Verukozni karcinom - Hodl, Stephan (Radiology and oncology (Ljubljana), 1999)
Verrucous is a rare clinical picture of the skin cancer. It is a disease of low malignancy. Usual locations are on the skin, in the oropharyngeal mucosa and in the genitoanal region. Verrucous carcinoma is a chronic disease, with alate proggression in the regional lymph nodes. In the differential diagnostics, plantar warts, keratoacanthoma, amelanotic malignant melanoma as well as different pyodermias have to be excluded. Early surgical tratment usually means a total recovery for patients.
Keywords: Carcinoma, verrucous; Skin neoplasms